Tinjauan Hukum Pengunaan Aplikasi inDriver MOD Menurut Fatwa MUI Nomor 1/MUNAS VII/MUI/5/2005 Tentang Hak Kekayaan Intelektual - Sutan Fahri; Khalid Khalid (LPPM Universitas Ekasakti Padang, 2023)
Several large companies are racing to establish app-based transportation companies, and one of them is inDriver. The inDriver app, particularly for drivers, is not immune to application modifications. One of the widely circulated modified applications among drivers is the inDriver MOD Autobid. Given the high interest and usage of inDriver by the public for their daily needs, it's undeniable that the number of inDriver drivers has significantly increased, intensifying the competition among them for orders.Despite this, the inDriver order system is still the one assigning orders to drivers, rather than a